If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 93 = -7x + -5x + -3 Reorder the terms: 93 = -3 + -7x + -5x Combine like terms: -7x + -5x = -12x 93 = -3 + -12x Solving 93 = -3 + -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. 93 + 12x = -3 + -12x + 12x Combine like terms: -12x + 12x = 0 93 + 12x = -3 + 0 93 + 12x = -3 Add '-93' to each side of the equation. 93 + -93 + 12x = -3 + -93 Combine like terms: 93 + -93 = 0 0 + 12x = -3 + -93 12x = -3 + -93 Combine like terms: -3 + -93 = -96 12x = -96 Divide each side by '12'. x = -8 Simplifying x = -8
| -17x-20=-14x+115 | | 5m+7n=39 | | y=2x^2-6x-26 | | 7p+4q=43 | | 12C+C=7C+18 | | 3g-49=47 | | 5m+7n=35 | | x^4-11x^2+28=x | | 6-y=2y | | 6n+10=3 | | 9(1+9k)= | | 0.14=0.0001 | | u^2+250=0 | | M^2+3M= | | -15/-5=3 | | 0.13=0.001 | | x-7.5=-2x | | -6x=4y+1 | | 14+3n=8n-3+(n-4) | | 8(4-M)=8+4M | | 2l=5l-60 | | 88.1-2.3=72.46 | | 0.12=0.01 | | 200000+(60)=300000+(25) | | 3=3+5k-5 | | 6x+5=2x-3 | | 12+(x+9)=7 | | 2l=60-5l | | -42p-4p=-12 | | -15.3=7.5+55.2 | | 35(100000)= | | 0=-4.9t^2+19.6t+58.8 |